Analysis of Judges' Considerations Regarding Divorce Lawsuits Caused by Domestic Disputes - Eka Kristina Sinaga; July Esther (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Analyzing the Legal Considerations of the Panel of Judges in deciding a divorce lawsuit caused by domestic disputes, by examining the legal reasons used as the basis for decision making. Identifying factors that influence the judge's decision, both objective and subjective, such as evidence presented, reconciliation efforts, and social or psychological impacts on married couples and children. This research uses a normative research method, which is a research method that focuses on the analysis of applicable legal norms, both in statutory regulations and court practice. This research aims to analyze the legal considerations of the panel of judges in deciding divorce lawsuits caused by domestic disputes, by referring to relevant legal regulations and court decisions. Based on the research results, it can be concluded that the panel of judges' legal considerations regarding divorce lawsuits caused by domestic disputes are very complex and involve various legal, social and psychological factors. Limitations in Analyzing Psychological and Social Factors: Judges' considerations often involve deep psychological factors related to family dynamics, but these factors are difficult to analyze objectively by relying solely on legal documents and court decisions. This research has the potential to make a significant contribution to improving family law practice in Indonesia, improving existing legal processes, and having a positive impact on individuals and communities involved in divorce